2003
DOI: 10.2136/vzj2003.0052
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Flow during Redistribution in Homogeneous Soil

Abstract: sary conditions for the onset of fluid instability. The most widely studied and documented occurrences of unstable Two-and three-dimensional laboratory experiments were conflow in the vadose zone are of two types: vertical flow ducted in a large 1 by 1 m 2 Hele-Shaw cell and a 10-cm cylinder column to study the stability of the redistribution process in a uniformly from a fine-textured layer into a coarse one (Hill and packed porous medium of coarse sand. Our results demonstrate that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 4 publications
(7 reference statements)
1
28
3
Order By: Relevance
“…The field observations of funnel flow in the dam farmland proved the existence of this phenomenon which was reported by prior researchers (Miyazaki 1988;Kung 1990;Walter et al 2000;Heilig et al 2003;Gish et al 2003), but not "fingers" reported by Hill and Parlange (1972), Samani et al (1989), and Wang et al (2003). This can be explained that the "fingers" are very small with the diameter of only several centimeters, about 4 cm by Hill and Parlange (1972), about 6.8 ± 2.2 cm in mean size by Wang et al (2003). They could not be easily observed in the dam farmland for the relative large scale.…”
Section: Funnel Flow Observationssupporting
confidence: 62%
“…The field observations of funnel flow in the dam farmland proved the existence of this phenomenon which was reported by prior researchers (Miyazaki 1988;Kung 1990;Walter et al 2000;Heilig et al 2003;Gish et al 2003), but not "fingers" reported by Hill and Parlange (1972), Samani et al (1989), and Wang et al (2003). This can be explained that the "fingers" are very small with the diameter of only several centimeters, about 4 cm by Hill and Parlange (1972), about 6.8 ± 2.2 cm in mean size by Wang et al (2003). They could not be easily observed in the dam farmland for the relative large scale.…”
Section: Funnel Flow Observationssupporting
confidence: 62%
“…However, Diment and Watson's (1985) experiments in a small slab box showed that redistribution “stabilized” when the initial water content was increased to only a few percent of saturation. In contrast, recent experiments of Wang et al (2003a)(2003b) in the field and with a large slab box showed that redistribution is unstable even in a very wet uniform sand. Nicholl et al (1994) observed fingering during redistribution in initially dry fractures.…”
mentioning
confidence: 71%
“…The length of this zone is equal to the capillary suspension length ( S ). Since the water‐entry value ( h we ) decreases as initial water content θ i increases (Smith, 1967; Liu et al, 1994; Wang et al, 2003a), the blob is longer in relatively moist soils than in dry soils.…”
Section: Theorymentioning
confidence: 99%
“…Raats (1973) explained that an increase of soil water pressure with depth above the wetting front in general leads to instabilities of the wetting front. Entrapment of air, the presence of layers with higher water‐entry values, water repellency, but also the reversal of pressure gradients during redistribution just after infiltration at the soil surface has ceased can cause such an increase in pressure above the wetting front that leads to unstable wetting fronts (Wang et al, 1998, 2003a, 2003b). Another process, which originates at the pore scale and which can explain the persistence of individual fingers due to pressure increase or pressure overshoot above the wetting front of a single finger, is the dynamic pressure–water content relation that results from a rapid filling of larger pores and a subsequent redistribution (DiCarlo, 2013).…”
Section: Improving the Infiltration Process In Land Surface Modelsmentioning
confidence: 99%